INOVASI PENGENDALIAN HAMA TIKUS MENGGUNAKAN PUKAT ANTI TIKUS PADA TANAMAN PADI SAWAH DI KELURAHAN SENDANG MULYA SARI KECAMATAN TONGAUNA KABUPATEN KONAWE - Hendrikus Robi; Rosmawaty Rosmawaty; Mardin Mardin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
Rats have been identified as a significant threat to rice productivity in Indonesia, including in Sendang Mulya Sari Village in the Tongauna Subdistrict of Konawe Regency, a region that is a major producer of rice. The objective of this study is to analyze the manufacturing process, steps for use, characteristics of innovation, and effectiveness of the Anti-Rat Net as an alternative for controlling rats in rice fields. The research was conducted using a qualitative approach through a purposive study in Sendang Mulya Sari Village, involving 18 informants who were purposively selected from 11 rice farming groups. The research concentrated on the methodologies for fabricating and utilizing the Anti-Rat Net, emphasizing its innovative attributes. The findings indicated that the Anti-Rat Net exhibited a substantial capacity to curtail the severity of rat pest incursions, accompanied by a notable capture success rate and a comparatively low operational cost efficiency when benchmarked against established methodologies. The Anti-Rat Net innovation is characterized by its adaptability to farmers' needs and ease of application. The present study corroborates the hypothesis that the Anti-Rat Net can function as an effective solution for sustainable rat pest control.